Pengaruh Korean Wave Dan Brand Ambassador Pada Keputusan Pembelian Handphone Samsung Dan Gaya Hidup Konsumen Di Makassar - Widya Tibayan; Fransiska Mawar; Andryanus Paridi; Jerliyen Pramita Londong (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This research aims to see the influence of the Korean Wave and Brand Ambassador on consumer purchasing decisions for Samsung cellphones and consumer lifestyles in Makassar City. This research is qualitative research carried out in the city of Makassar from September to November 2023. The sample in this research was taken from as many as 50 people using a purposive sampling technique. Data was collected through a questionnaire, and then processed with a statistical application using SmartPLS version 4.0. From the research results it was found that: Korean Wave has no influence on the purchasing decisions of Samsung mobile phone consumers in the city of Makassar, Korean wave has a positive and significant effect on the lifestyle of consumers in the city of Makassar, Brand ambassador has a positive and significant effect on the purchasing decisions of Samsung mobile phone consumers in the city of Makassar, and brand ambassadors have a positive and significant influence on consumer lifestyles in the city of Makassar.